TANGGUNG JAWAB MAXIM ATAS KLAUSULA EKSONERASI DALAM KONTRAK ELEKTRONIK TRANSPORTASI ONLINE - Aloysius S; Maryati Bachtiar; Ricki Musliadi (Peneliti.net, 2026)
Online transportation in Indonesia has emerged as a solution to the suboptimal conventional transportation system, characterized by severe congestion and poor public transportation. Using the app requires agreement to a standard contract during registration that is unilaterally set by the service provider. A crucial issue arises from the exoneration clause, which shifts the business actor's responsibility to the consumer, contradicting Article 18 paragraph 1A letter (a) of Law No. 8 of 1999 on Consumer Protection (UUPK). A concrete example is seen in the Maxim app, where Service Performance Regulation Number Seven contains such a clause. This study employs a normative legal research method, focusing on analysis of legal norms, laws, and related documents to uncover the legal implications of standard agreements in online transportation. The findings indicate that if a standard clause contains an exoneration clause, such clause shall be declared null and void by law. Furthermore, to obtain the rights of aggrieved consumers, dispute resolution between Maxim and consumers can be pursued through BPSK (Consumer Dispute Settlement Agency) and the Judicial Institution.